Amyloban, extracted from Hericium erinaceus, ameliorates social deficits and suppresses the enhanced dopaminergic system in social defeat stress mice - Tianran Wang; Kazuya Toriumi; Kazuhiro Suzuki; Mitsuhiro Miyashita; Azuna Ozawa; Mayuko Masada; Masanari Itokawa; Makoto Arai (Neuropsychopharmacology Reports)
Abstract Social dysfunctions are common in various psychiatric disorders, including depression, schizophrenia, and autism, and are long‐lasting and difficult to treat. The development of treatments for social impairment is critical for the treatment of several psychiatric disorders. “Amyloban 3399,” a product extracted from the mushroom Hericium erinaceus, markedly improves social dysfunctions in patients with treatment‐resistant schizophrenia and depression. However, the molecular mechanism(s) through which amyloban ameliorates social impairment remains unclear. To clarify this mechanism, in this study, we aimed to establish a mouse model of social defeat stress (SDS) and investigate the effects of amyloban on social deficits. Amyloban administration ameliorated social deficits and the dopamine system activity in SDS mice. These findings suggest that there is a possibility that amyloban may improve social deficits by suppressing the hyperactivation of the dopaminergic system. Amyloban may be an effective treatment for social dysfunctions associated with various psychiatric disorders.